Mountains : A Very Short Introduction - Price, Martin F. (Oxford, New York Oxford University Press, 2015)
In this introduction, Martin Price addresses the role of mountains in global ecosystems and within human culture. Considering the global effects of melting glaciers, and the conservation of mountain regions and peoples, he discusses the future of mountainous regions and the implications for all of us.
Include Illustration and Index
Keywords: Mountains -- Mountain ecology